Espaço sagrado e performances de corpo: o caso do Terreiro de Umbanda Reino de Jurema em Santa Maria/RS - Santos, Mateus Machado (2019)
The current research presents the results of a investigation of a Master Course accomplished at university federal de Santa Maria, UFSM/RS. The research focused on the epistemic field of cultural geography, more specifically in the geography of Religion. The premise was the understanding of the sacred space and the body performances in the Terreiro de Umbanda Reino de Jurema in the city of Santa Maria/RS. Its purpose was to investigate and problematize the Terreiro Reino de Jurema as a sacred space of umbanda as well as its performative meaning of body in the moment of the charitable sessions, inciting the relations between Researcher- researched in this study. The proposal of this investigation, from the chosen object, was designed from his experiences as medium in the own terreiro, ransoming interdisciplinary relations between the universe of arts and geography. we choose for a qualitative investigation, focused on the theoretical concepts of a participant observation and biographical(self) narratives. The methodological approaches were divided into three phases. the first step remembered the knowledge of the universe of the research theme. In the second and third stages theoretical and practical paths were recognized to think about how the production of sacred space and body performances were established, from the charitable sessions. The field observations in the terreiro Reino de Jurema were from September 2017 to November 2018.The data collection instruments performed in the second research stage, the main core of the research were: diary of field, photography record, videos and semi structured interview. In this context, seeking in the body a way of thinking the space, helped us to understand how the way the symbolic- religious thought was manifested through the ritualistic of Umbanda. that thought was reflected in a plural identity found in the terreiro Reino de Jurema.